PENDAMPINGAN DESA DALAM PENGUATAN DEMOKRASI DAN GOOD GOVERNANCE DI DESA SAYAMBONGIN KEC. NAMBO KAB. BANGGAI - Hartati, Andi; Palopa, Rahmad; Mahmud, Siska (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2023)
"The mentoring initiative in Sayambongin Village, Nambo District, Banggai Regency, has an urgency in strengthening democracy and good governance. The focus is increasing community participation, strengthening village institutions such as BPD and LPM, and improving the quality of village governance. The main objectives include increasing awareness and community participation, empowerment of BPD and LPM, as well as increasing the capacity of officials and improving the administrative system. The expected outcomes involve increasing community participation, strengthening village institutions, improving government governance, and increasing community understanding of democracy and good governance. This assistance involves the collaboration of service teams community, village government, local institutions and the people of Sayambongin Village, with the hope of creating a village that is participatory, transparent and accountable in managing public affairs." ABSTRAK"Inisiatif pendampingan di Desa Sayambongin, Kecamatan Nambo, Kabupaten Banggai, memiliki urgensi dalam penguatan demokrasi dan good governance. Fokusnya adalah meningkatkan partisipasi masyarakat, memperkuat lembaga desa seperti BPD dan LPM, serta meningkatkan kualitas tata kelola pemerintahan desa. Tujuan utama mencakup peningkatan kesadaran dan partisipasi masyarakat, pemberdayaan BPD dan LPM, serta peningkatan kapasitas aparat dan perbaikan sistem administrasi. Luaran yang diharapkan melibatkan peningkatan partisipasi masyarakat, penguatan lembaga desa, perbaikan tata kelola pemerintahan, dan peningkatan pemahaman masyarakat tentang demokrasi dan good governance. Pendampingan ini melibatkan kerjasama tim pengabdian masyarakat, pemerintah desa, lembaga lokal, dan masyarakat Desa Sayambongin, dengan harapan menciptakan desa yang partisipatif, transparan, dan akuntabel dalam mengelola urusan publik."